Evolution of Communication Studies: A Review - Yadav, Aditya Kumar (Journal of Advanced Research in Humanities and Social Sciences, 2024)
Communication Studies, as an interdisciplinary field, has witnessed significant evolution over the years, driven by advancements in technology, changes in societal norms, and theoretical developments. This review article explores the historical trajectory of Communication Studies, highlighting key milestones, theoretical frameworks, methodological approaches, and emerging trends. It examines how the field has adapted to address contemporary challenges and opportunities, including digital communication, globalization, and cultural diversity. By synthesizing diverse perspectives, this review provides insights into the past, present, and future directions of Communication Studies.